2020
DOI: 10.1039/c9ra08881d
|View full text |Cite
|
Sign up to set email alerts
|

Effects of oxygen on the structural evolution of polyacrylonitrile fibers during rapid thermal treatment

Abstract: Oxygen has significant influence on both the chemical and physical structural evolution of PAN fibers during rapid stabilization.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
9
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 24 publications
(9 citation statements)
references
References 35 publications
0
9
0
Order By: Relevance
“…4(a) and (b) show that the stabilization degrees (FNs and DHI) in the skin region were higher than in the core region, which was because, during the thermal stabilization, the fibre's outer layer was first exposed to oxygen, which could subsequently promote cyclization, dehydrogenation and oxidation reactions to facilitate the increase in FNs and DHI. 40 When TTI < 6.37 × 10 5 s K, decreasing trends were observed in response to the stabilization degrees in the skin region, while the trends for the stabilization degrees were converted into upward at a TTI adjustment of 6.37 × 10 5 s K. Since this may because the skin regions of the SFs were first influenced by the radial diffusion of oxygen, a relatively larger stabilization degree during a short duration time depends on a much higher stabilization temperature. 8 Conversely, the main contributor to the increased stabilization degrees was responsible for the prolonged stabilization time.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…4(a) and (b) show that the stabilization degrees (FNs and DHI) in the skin region were higher than in the core region, which was because, during the thermal stabilization, the fibre's outer layer was first exposed to oxygen, which could subsequently promote cyclization, dehydrogenation and oxidation reactions to facilitate the increase in FNs and DHI. 40 When TTI < 6.37 × 10 5 s K, decreasing trends were observed in response to the stabilization degrees in the skin region, while the trends for the stabilization degrees were converted into upward at a TTI adjustment of 6.37 × 10 5 s K. Since this may because the skin regions of the SFs were first influenced by the radial diffusion of oxygen, a relatively larger stabilization degree during a short duration time depends on a much higher stabilization temperature. 8 Conversely, the main contributor to the increased stabilization degrees was responsible for the prolonged stabilization time.…”
Section: Resultsmentioning
confidence: 99%
“…According to some studies, it has been found that some stabilization reactions, including cyclization, dehydrogenation, and oxidation reactions, are initiated at the amorphous PAN chains, and then gradually expand to the ordered region with the progression of stabilization reactions. 40 This finally results in crystal PAN chains being destroyed and disordered, becoming new amorphous chain regions that can process other stabilization reactions. Therefore, combined with the stabilization degrees results discussed in the previous section, the evolution trend of the aggregate structures both in the skin and core regions was opposite to that of the stabilization degrees.…”
Section: Resultsmentioning
confidence: 99%
“…24 Also, the presence of oxygen greatly facilitates the cyclization and dehydrogenation of PAN at temperatures above 200 °C. 25 In this report, we demonstrate that coating of PAN followed by a simple heat treatment in air can greatly improve the electrochemical performance and cycling stability of NMC811 in a sulfide-based solid state battery.…”
mentioning
confidence: 77%
“…Specialty literature shows that PAN changes color only when it is subjected to thermal treatment at above 240 • C during stabilization, as the first stage of PAN conversion into carbon fiber [14]. Color appears as result of the formation of the polyimine cycle in nitrogen [15], oxygen [16][17][18][19] or air [20], at high temperature. Stabilization in a mixture of air and ammonia, NH 3 at 260 • C turns PAN's color from white to yellow and finally to black, depending on treatment severity [21].…”
Section: Introductionmentioning
confidence: 99%
“…Chemical and physical changes in the PAN structure are insignificant if the treatment is performed at temperatures below 140 • C. Above this temperature, oxygen in the air can sensitize the nitrile group (polyimine cycles occur) and cause crosslinking between the macromolecular chains of PAN [19,22].…”
Section: Introductionmentioning
confidence: 99%